Venous and Arterial Responses to Partial Gravity - Lee, Stuart M. C.; Martin, David S.; Miller, Christopher A.; Scott, Jessica M.; Laurie, Steven S.; Macias, Brandon R.; Mercaldo, Nathaniel D.; Ploutz-Snyder, Lori; Stenger, Michael B. (Frontiers in Physiology, 2020)
Introduction: Chronic exposure to the weightlessness-induced cephalad fluid shift is hypothesized to be a primary contributor to the development of spaceflight-associated neuro-ocular syndrome (SANS) and may be associated with an increased risk of venous thrombosis in the jugular vein. This study characterized the relationship between gravitational level (Gz-level) and acute vascular changes. Methods: Internal jugular vein (IJV) cross-sectional area, inferior vena cava (IVC) diameter, and common carotid artery (CCA) flow were measured using ultrasound in nine subjects (5F, 4M) while seated when exposed to 1.00-Gz, 0.75-Gz, 0.50-Gz, and 0.25-Gz during parabolic flight and while supine before flight (0-G analog). Additionally, IJV flow patterns were characterized. Results: IJV cross-sectional area progressively increased from 12 (95% CI: 9–16) mm2 during 1.00-Gz seated to 24 (13–35), 34 (21–46), 68 (40–97), and 103 (75–131) mm2 during 0.75-Gz, 0.50-Gz, and 0.25-Gz seated and 1.00-Gz supine, respectively. Also, IJV flow pattern shifted from the continuous forward flow observed during 1.00-Gz and 0.75-Gz seated to pulsatile flow during 0.50-Gz seated, 0.25-Gz seated, and 1.00-Gz supine. In contrast, we were unable to detect differences in IVC diameter measured during 1.00-G seated and any level of partial gravity or during 1.00-Gz supine. CCA blood flow during 1.00-G seated was significantly less than 0.75-Gz and 1.00-Gz supine but differences were not detected at partial gravity levels 0.50-Gz and 0.25-Gz. Conclusions: Acute exposure to decreasing Gz-levels is associated with an expansion of the IJV and flow patterns that become similar to those observed in supine subjects and in astronauts during spaceflight. These data suggest that Gz-levels greater than 0.50-Gz may be required to reduce the weightlessness-induced headward fluid shift that may contribute to the risks of SANS and venous thrombosis during spaceflight.